Engineering a Copper Single‐Atom Electron Bridge to Achieve Efficient Photocatalytic CO2 Conversion. (20th February 2023) - Wang, Gang; Wu, Yan; Li, Zhujie; Lou, Zaizhu; Chen, Qingqing; Li, Yifan; Wang, Dingsheng; Mao, Junjie
Abstract: Developing highly efficient and stable photocatalysts for the CO2 reduction reaction (CO2 RR) remains a great challenge. We designed a Z‐Scheme photocatalyst with N−Cu1 −S single‐atom electron bridge (denoted as Cu‐SAEB), which was used to mediate the CO2 RR. The production of CO and O2 over Cu‐SAEB is as high as 236.0 and 120.1 μmol g −1 h −1 in the absence of sacrificial agents, respectively, outperforming most previously reported photocatalysts. Notably, the as‐designed Cu‐SAEB is highly stable throughout 30 reaction cycles, totaling 300 h, owing to the strengthened contact interface of Cu‐SAEB, and mediated by the N−Cu1 −S atomic structure. Experimental and theoretical calculations indicated that the SAEB greatly promoted the Z‐scheme interfacial charge‐transport process, thus leading to great enhancement of the photocatalytic CO2 RR of Cu‐SAEB. This work represents a promising platform for the development of highly efficient and stable photocatalysts that have potential in CO2 conversion applications. Abstract : Copper single‐atom electron bridges (SAEB) were constructed at the contact interface between Cu1 /MoS2 and MIL‐125‐NH2 to achieve a highly active and stable catalyst for CO2 photoreduction. Empowered by the N−Cu1 −S SAEB species, the Z‐Scheme charge‐transfer process was significantly promoted, leading to enhancement of the photocatalytic CO2 RR.